EVALUATION OF ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF VERNONIA AMYGDALINA LEAF EXTRACTS AS AN AUXILIARY IN NATURAL HAIR SHAMPOO - TINRAT, SIRIKHWAN; SINGHAPOL, CHATCHAWAN (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study evaluated the phytochemical compounds, antioxidant, and antimicrobial activities of Vernonia amygdalina (VA) leaf extract and used it as an auxiliary herbal constituent in natural hair shampoo. Methods: VA leaf was macerated in various solvents. All crude extracts were phytochemical compounds screened and determined the antioxidant and antimicrobial activities before formulating a natural shampoo formula. Natural shampoos were evaluated with physic-chemical properties and sensory satisfaction. Results: About 95% ethanolic extract was the most suitable substrate for product development. It reveals the inhibition zone from 7.00±0.00 to 15.00±1.00 mm and possesses a broad spectrum of antibacterial agents against both Gram-positive and Gram-negative bacteria. The MICs and minimum bactericidal concentrations value ranged from 6.250 to 100 mg/ml and 25 to >200 mg/ml, respectively. About 95% ethanolic extract also revealed high antioxidant activity. The IC50 value of DPPH of 95% ethanolic extract was 1.88±0.02 μg/ml (% inhibition of 85.73±0.01) and the ferric reducing ability power was 23.00±0.50 mg AAE/100 gDW. These high biological activities may be due to a broad range of phytochemical compounds, including saponins, tannins, flavonoids, terpenoids, steroids, cardiac glycosides, and alkaloids. Conclusions: The VA leaf was suitable to use as an ingredient in natural shampoos with a low detrimental effect on normal skin flora. The shampoo with 0.00188% of 95% ethanolic extract was the most suitable formula in terms of characteristics and stability. This formula also obtained the highest satisfaction level under our sensory evaluation.